2016
DOI: 10.3847/0004-637x/816/2/54
|View full text |Cite
|
Sign up to set email alerts
|

A Chandra Study of Temperature Distributions of the Intracluster Medium in 50 Galaxy Clusters

Abstract: To investigate the spatial distribution of the intracluster medium temperature in galaxy clusters in a quantitative way and probe the physics behind it, we analyze the X-ray spectra from a sample of 50 clusters that were observed with the Chandra ACIS instrument over the past 15 years and measure the radial temperature profiles out to 0.45r 500. We construct a physical model that takes into consideration the effects of gravitational heating, thermal history (such as radiative cooling, active … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The abundance was fixed at the standard value of 0.3 Z . Similar to the results presented in Zhu et al (2016), the temperature of the cluster as a function of radius was found to be flat out to r 500 .…”
Section: Total Spectrum Of Primary Cluster and Bcg2 Subclustersupporting
confidence: 85%
“…The abundance was fixed at the standard value of 0.3 Z . Similar to the results presented in Zhu et al (2016), the temperature of the cluster as a function of radius was found to be flat out to r 500 .…”
Section: Total Spectrum Of Primary Cluster and Bcg2 Subclustersupporting
confidence: 85%
“…We find that the azimuthally averaged projected gas temperature shows a small increase from 3.20 +0.15 −0.16 keV in the innermost region (< 0 .6 or 48.6 kpc) to 4.15 ± 0.17 keV at ∼ 1 (∼ 81 kpc), and a gradual descent in 2 , which agrees with the temperature profile obtained with the Chandra ACIS data in the W sector ( §3.2). This profile is similar to those obtained in other galaxy clusters, which typically show an outward temperature increase in the inner regions to a peak value at ∼ 0.2r 500 and then a continuous temperature drop out to about r 500 (Zhu et al 2016), implying that within about 0.2r 500 the thermodynamic effect of the gravity has been greatly modified by the effects of non-gravitational processes (essentially radiative cooling and AGN feedback), while in outer regions the gravity dominates the gas thermodynamics (Zhu et al 2021). The azimuthally averaged projected metal abundance shows a significant peak of 0.89 +0.18 −0.16 Z in the innermost region (< 0 .6 or 48.6 kpc) and a monotonous outward decrease to a very low value (∼ 0.1 Z ) in the outermost annuli.…”
Section: Azimuthally Averaged Spectral Analysis With Xmm-newton Datasupporting
confidence: 88%
“…The gas and total gravitational masses of Abell 1775 can be determined by applying a revised thermodynamical ICM (RTI) model provided by Zhu et al (2016Zhu et al ( , 2021, which takes into account the effects of both gravitating and non-gravitational processes (e.g., feedback and radiation). In the RTI model, the total gravitational mass is described by using the generalized NFW profile (Navarro, Frenk & White 1997)…”
Section: Spatial Distributions Of Gas Mass and Total Gravitational Massmentioning
confidence: 99%
“…However, a Dressler and Shectman three-dimensional test of the galaxy redshifts suggests that the cluster is disturbed (Lopes et al 2018). The radius of the cluster is R 500 = 1.56 ± 0.06, 1.1 +0.3 −0.1 Mpc depending on the mass estimate, which is debated between the values M 500 = 11.7 ± 1.4, 4.0 +5.2 −1.1 , and 3.73 +0.18 −0.19 , in units of 10 14 M , derived from radial velocity distribution, Chandra and Planck data, respectively (Planck Collaboration XXVII 2016; Zhu et al 2016;Lopes et al 2018). At larger radii, R 200 = 2.2 ± 0.1 Mpc and M 200 = 12.7 ± 1.5 × 10 14 M (Lopes et al 2018;Oh et al 2018).…”
Section: General Properties Of Abell 2249mentioning
confidence: 99%